Two Aspects to Consider in the Adoption of Embryos by the State of Querétaro: the Child’s Right to know their Genetic Origin and the Implicit Prohibition of Pre-implantation and Prenatal Diagnosis (Revista Iberoamericana de Bioética, 2017)
In the implementation of heterologous assisted reproduction procedures, the donation of supernumerary embryos is a constant in current regulation. In Mexico, the State of Queretaro is unique in how it regulates this legal act, so important for relationships sustained under current family law: it allows infertile couples the opportunity to adopt supernumerary embryos. This paper analyses two essential aspects: the child’s right to know their genetic origin and the implicit prohibition of prenatal and preimplantation genetic diagnosis, giving rise to various legal implications.
Keywords: Bioethics; preimplantation genetic diagnosis (PGD); prenatal genetic diagnosis; embryo adoption; genetic origin; assisted reproduction (AR)